Analysis of expression levels of markers associated with tumor proliferation and angiogenesis in familial adenomatous polyposis. Issue 12 (27th October 2020) - Zhang, Zhao; Wang, Dan; Xu, Chen; Li, Yuwei; Yu, Yongjun; Chen, Chao; Li, Mingsen; Zhang, Xipeng
Abstract: Background: Familial adenomatous polyposis (FAP) is an autosomal dominant hereditary disease with colorectal adenomatous polyps as the main clinical manifestations. The objective of this study was to analyze and compare the expression levels of tumor proliferation and angiogenesis‐related genes in different tissue sections of FAP patients through qPCR, western blot, and immunohistochemistry (IHC) analysis. Methods: Seventeen patients with FAP admitted to Tianjin Union Medical Center from January 2010 to June 2015 were selected, and then, normal intestinal mucosa, polyp tissue, or cancerous polyp tissue were collected. QPCR, western blot, and IHC were used to detect the expression level of genes or proteins correlated with tumor proliferation. Results: The mRNA expression of CD31 in large polyp tissue was significantly higher than that in normal tissue and small polyp tissue. Compared with normal tissue and polyp tissue, the expression level of KI67 mRNA in cancer tissue was remarkably increased. The VEGFA mRNA and CDH5 mRNA expression in both polyp and cancer tissues were prominently lower than those in normal tissue. The expression of CD31 protein in cancer tissue was lower than that in normal tissue and polyp tissue, whereas the expression levels of VEGF, CDH5, and KI67 protein were widely higher than that in normal tissue and polyp tissue. Conclusion: Abnormal expressions of CD31, KI67, VEGF(A), and CDH5 were associated with the carcinogenesis of FAP. Abstract : To analyze and compare the expression levels of tumor proliferation and angiogenesis‐related genes in different tissue sections of FAP patients through qPCR, western blot and immunohistochemistry (IHC) analysis. We find that abnormal expressions of CD31, KI67, VEGF(A), and CDH5 were associated with the carcinogenesis of FAP.